(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This article evaluates thenovel They Die Strangers (1972) by the Yemeni novelist Mohammed Ahmed Abdul Wali as a postcolonial narrative of emigration inwhich the writer argues about what is called the ideology of return. Anemigrant himself, the writer discusses the impact of long- term emigration on the individual, his family and the society as a whole. The discussion, using a postcolonialperspective, covers issues related to the construction of the Yemeni identity, body politics, the Yemeni farmers‟ dream and the representation of women focusing on the body-land association. The discussion concludes with considering the novel as a parody againstthose who migrate leaving their women and their land behind, only to live anddie as strangers.